PENGARUH KEPUASAN KERJA TERHADAP TURNOVER INTENTION DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL MODERATING PADA SEBUAH BANK PERKREDITAN RAKYAT DI KOTA BANDUNG - Ikhtikafi Rosyida, - (2020)
The problem examined in this study is the high level of turnover intention at a Rural Bank in Bandung, seen from the turnover intention from year to year. This study consists of three variables, namely job satisfaction as the dependent variable, turnover intention as the independent variable and organizational commitment as the moderating variable. This study aims to describe the level of job satisfaction, turnover intention and organizational commitment. In addition, this study aims to determine the effect of job satisfaction on turnover intention which is moderated by organizational commitment to a Rural Bank in Bandung City. The research method used is explanatory survey method, with data collection techniques using questionnaires. This research is a population study with 30 respondents. Respondents in this study were all employees at a Rural Bank in Bandung City. And the data analysis techniques used are simple regression analysis and Moderated Regression Analysis (MRA) Based on the analysis of the research results, it is found that the level of job satisfaction is in the high category. The picture of the level of turnover intention is in the medium category and the picture of the level of organizational commitment is in the high category. Meanwhile, the results of hypothesis testing in this study indicate that job satisfaction has a negative and significant effect on turnover intention. And organizational commitment is a moderating variable that strengthens the effect of job satisfaction on turnover intention at a Rural Bank in Bandung City.